Study of modified zeolites as heterogeneous catalysts for synthesis of petrochemicals and other organic compounds - Gautam, Priyanka (My University, 2023)
The thesis thoroughly covers the esterification of glycerol and levulinic acid, transesterification of glycerol, and alkylation of indole. Esterification, transesterification, and alkylation of low-valued chemicals were done so as to convert these to industrially important products like monoacetin, diacetin, glycerol carbonate, levulinate ester, and indole derivatives etc. Various homogeneous and heterogeneous catalysts such as HZSM-5, USY, Beta, and ammonium form of mordenite zeolites were used in the esterification, transesterification, and alkylation reactions. A detailed description of the catalyst such as its composition, structure, and properties has been discussed. In order to enhance the catalyst activity and reactivity towards the desired reaction, zeolites were further altered with various metals and functional groups. In order to understand, the influences of loading on the catalytic performance of the zeolites, yield, and selectivity of the product in specific reactions, characterization of catalysts was done by EDS, XRD, FE-sSEM, HRTEM, XPS, DLS, BET, and TPD. The reactant conversion depends on the activity of the catalyst, catalyst loading, reactant mole ratio, and reaction temperature. The outlined mechanisms of different reactions showed that the catalyst pore size and the type of pore as well as the feed composition of binary mixtures play important roles in the formation of the desired product. The activity of the zeolite also depends on the type of ions exchanged with the Na+ and H+ ions present in the framework of the zeolite. Besides evaluating the catalytic performance, the kinetic parameters of the reactions were also evaluated. The activation energy for the transesterification reaction was found to be 34.60 kJ/mol. The activation energy for the esterification reaction of glycerol with acetic was found to be 63.72 kJ/mol and for levulinic acid and ethanol esterification, it came out to be 19.57 kJ/mol. In the esterification of glycerol, 98.32% conversion of glycerol was obtained at optimized reaction conditions with a mixture of monoacetin and diacetin which are used as precursors in the food, cosmetic industries etc. The catalyst was reused for 4 reaction cycles. The reaction follows pseudo-first-order reaction kinetics. The esterification reaction of levulinic acid with ethanol was performed using sulfuric acid-modified zeolite Y catalyst which produced 96% ethyl levulinate which is directly used as Diesel Miscible Biofuel in car engines. To check the x stability of the catalyst, it was reused for up to 4 cycles. The esterification of levulinic acid with ethanol followed pseudo-first-order reaction kinetics. Glycerol and dimethyl carbonate were transesterified using a Li-modified zeolite beta catalyst which produced 81.48% glycerol carbonate at optimized reaction conditions and it is used in pharmaceuticals, paints industries etc. The catalyst was reused for up to 5 reaction cycles with 100% selectivity of glycerol carbonate. The experimental data followed second-order reaction kinetics. The sulfuric acid-treated mordenite (SO3H@Mor) zeolite was used as a catalyst for the synthesis of 3-alkylated indole from indole and methyl vinyl ketone which is a good precursor for anti-cancer treatment. A maximum of 92% β-alkylated indole was obtained with no side product. The catalyst was reused for up to 3 reaction cycles. The system followed a pseudo-first-order reaction.
Keywords: esterification; heterogeneous catalysts; zeolites; glycerol carbonate; acetins; levulinate ester